Introduction: New Federalism - Theodore W. Ruger (Washington University Journal of Law & Policy, 2004)
Several intriguing and difficult questions about the federal-state allocation of power remain open even as we apparently near the end of the particular Rehnquist Court’s federalism initiative. New Justices on the Court and new initiatives by federal and state elected officials in the future will reshape this debate in ways that are perhaps unexpected and currently unforeseen. That the essays here are topically and methodologically diverse exemplifies the variety of this ongoing debate, which promises to continue throughout the next decade and beyond.
Keywords: Federal government; States& #x27; rights (American politics); Constitutional law